Menumbuhkan Jiwa Enterpreneur Mahasiswa - Achmad Ridlowi (Transformasi : Jurnal Studi Agama Islam, 2019)
This article intends to describe the phenomenon of unemployment that occur in our country is a major problem faced by the government. In countless number of unemployed continues to rise each day. The condition is caused due to the lack of jobs that exist today. The high level of unemployment menerminkan that the nation has not yet reached its welfare. Then how to solve that problem? Entrepreneurial activity became the backbone to reduce the level of unemployment that occur. Unfortunately, the Unia entrepreneurship in Indonesia has lagged behind the other countries. Why is that? Because the world of entrepreneurship in Indonesia rely more muscles than brains. Hard work compared with smart work. Nowadays we often see that each person is more likely to find jobs rather than create jobs. For example, the facts that happened a lot of graduates who took the test incoming civil servants. They still think that being an employee is a major step that is most appropriate to achieve the welfare of his life. Membludaknya students who took the test was not a success, but the low interest of students to entrepreneurship. That is why entrepreneurial activity in our country is said to be lagging behind other countries. Therefore, the need for improvement mindset. Both among governments and society. To that end, the public, especially among students who have a stock of knowledge and creativity gained in the world should have a mental pekuliahaan livelihood entrepreneurship compared with looking for work along with other unemployed looking for work anyway.